Masking or Unmasking the Evil? Polish Opinion-Forming Weeklies vis-à-vis the Crisis in the Roman Catholic Church in Poland - Paszenda, Joanna (Religions, 2023)
Almost twenty years have passed since the end of John Paul II’s pontificate. The Roman Catholic Church in Poland faces a serious crisis, stimulated not only by secularisation processes, which are characteristic for Western Europe, but also by a whole series of adverse events that unfolded at the end of the year 2020; they resembled a disaster marathon and had a considerable potential to attract media attention. A wide spectrum of Polish opinion-forming weeklies, ranging from left-liberal to ultra-conservative and far-right ones, as well as those associated with the Polish Episcopate, published accounts of the situation within the Catholic Church. In this manner, press discourse shaped the public perception of Catholicism in Poland. An analysis of the periodicals’ content disclosed a strong polarisation of opinions and a variety of interpretations. Differences between the particular weeklies were identified at the level of agenda-setting and prioritisation, framing, persuasion techniques employed, and additional contexts that were evoked, including the legal, moral, historical, philosophical, and religious ones.